PERANAN DINAS SOSIAL DAN PEMAKAMAN DALAM PEMBINAAN ANAK TERLANTAR DI KOTA PEKANBARU - Muhamad Deslyanto; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
One of the role of Social and Funeral Department of Pekanbaru City is children prosperity founding. Children are investment and future hope and also being next generation for the country. Children at least could grow and develope into physicaly and spiritualy healthy, smart, happy, high morality and honorable, because in the future they are asset that could determine the quality of nation’s civilization therefore they should get protection and education. That is the foundation for Social and Funeral Department of Pekanbaru City create special program for this case. Epecially Sosial Service and Empowerment Field strive for neglected children could empowered, build and protected is identify the amount of neglected children, founding and formulating technical guidance and controlling social service program in founding children prosperity field, and coordinated with other instance.organization that has duty for founding neglected children in Pekanbaru City.The purpose of this research in to knowing performance and knowing what factors that could be the obstacle for Social and Funeral Department of Pekanbaru City in founding The Owner of Social Prosperity Problem in Pekanbaru City. The theory that use are analysis tools in this research are role theory and organization theory. And the method that use for this research is descriptive qualitative methhod, that is reasearch means for getting systematic picture about the interest phenomoneon.Accoding to this reasearch result, the role of Social and Funeral Department of Pekanbaru City especially in the field of The Owner of Social Prosperity Problem in handling neglected children still not good. Efforts that The Owner of Social Prosperity Problem in handling neglected children like physicaly building such as sport and discipline training, sosial build such as ethics, leadership and citizenhip,spiritual build uch as pray together and reading Qur’an, mental build such as psychology that we invite from outside and for the last that is skill, skill in here is automotive 2 wheels transportation, and weld for the males, while for the females are skill for sewing and salon. However, in getting negleted children Social and Funeral Department of Pekanbaru City not yet reach their expected target. The obstacles that they have is limited human resource and also limited fund. The process for accompaniment neglected children that already builded should be until the children being independent. Supervision for accompaniment also need to do, if there is problem it should be overcome quicklyKey Words : Role, Government Organization, Children Founding.